A study of the relationship between cough and wheezing complicated by common respiratory viral infections in infants and secondary thrombocythemia. - Ping He; Fangqi Hu; Fei Wang (PLoS ONE, 2025)
Objective To explore the relationship between respiratory viral infections complicated by cough and wheezing and the clinical features of thrombocythemia in infants. Methods We retrospectively analyzed the clinical data of 200 infants with fever, cough and wheezing who were admitted to the Department of Pediatrics of Anqing Municipal Hospital between January 2023 and October 2024. Respiratory viruses were detected using real-time PCR to screen for virus-positive infants. Infants were classified into the thrombocythemia group (ST group) and the non-thrombocythemia group (non-ST group) based on platelet counts. We compared the clinical characteristics of the two groups and analyzed the relationships between thrombocythemia, positive respiratory virus results, and cough with wheezing. Results The overall virus positivity detection rate was 56.5% (113/200). In the ST group, patients with positive respiratory virus results had significantly longer hospital stays, higher fever incidence, and more severe cough symptoms (P < 0.05), and significantly higher leukocyte and interleukin-6 (IL-6) levels (P < 0.05). Among the virus-positive cases, the duration of fever, cough, and wheezing was longer in the ST group than in the non-ST group (P < 0.05). Higher platelet counts were significantly associated with longer hospitalization duration, prolonged cough duration and a higher co-occurring wheezing rate (p < 0.05). Point-biserial correlation analysis indicated that thrombocythemia was closely associated with respiratory virus positivity complicated by cough and wheeze (r = 0.314, P < 0.05). Multifactorial analysis revealed that age, non-respiratory symptoms, platelet levels, and IL-6 level were independent influencing factors for respiratory virus-positive infants with complicated cough and wheezing (P < 0.05). Receiver operating characteristic (ROC) curve analysis showed that the areas under the curve of thrombocythemia for assessing hospital stay duration and cough and wheeze durations were 0.964 and 0.936, respectively (P < 0.05), indicating a significant assessment value. Conclusion Infant respiratory viral infections complicated by cough and wheezing are closely related to secondary thrombocythemia. Elevated platelet levels can prolong the hospital stay and cough duration. The clinical risk in children can be assessed early by measuring platelet levels.